GE_GERICHTE P/22444/2014 vom 1. Juni 2017 - GE Cour de justice (2017)
DÉLAI DE RECOURS; RÉVISION(DÉCISION) ; CIRCULATION ROUTIÈRE(DROIT DE LA CIRCULATION ROUTIÈRE) ; RADAR | CPP.411; CPP.410; CPP.410; OSR.16; OSR.63; OSR.31